Older Primary Care Patients’ Attitudes and Willingness to Screen for Dementia - Nicole R. Fowler; Anthony J. Perkins; Hilary A. Turchan; Amie Frame; Patrick Monahan; Sujuan Gao; Malaz A. Boustani (Journal of Aging Research)
Objective. To understand older primary care patients’ perceptions of the risks and benefits of dementia screening and to measure the association between attitudes and screening behaviors. Methods. Eligible patients completed the Perceptions Regarding Investigational Screening for Memory in Primary Care (PRISM-PC) questionnaire and then were asked to undergo dementia screening by a telephone screening instrument. Results. Higher scores on the PRISM-PC questionnaire items that measure attitudes about benefits of screening were associated with decreased odds of refusing screening. Participants who refused screening had significantly lower PRISM-PC questionnaire scores on the items that measure perceived benefits compared to those who agreed to screening. Participants who refused screening were less likely to agree on screening for other conditions, such as depression and cancer. Participants who know someone with Alzheimer’s disease (AD) were less likely to refuse screening. Discussion. Patients’ attitudes about the benefits of dementia screening are associated with their acceptance of dementia screening.